2021
DOI: 10.3389/fimmu.2021.746492
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Bone Marrow Spheroids Reveal Leukemia-Initiating Cells Supported by Mesenchymal Hypoxic Niches in Pediatric B-ALL

Abstract: B-cell acute lymphoblastic leukemia (B-ALL) results from the expansion of malignant lymphoid precursors within the bone marrow (BM), where hematopoietic niches and microenvironmental signals provide leukemia-initiating cells (LICs) the conditions to survive, proliferate, initiate disease, and relapse. Normal and malignant lymphopoiesis are highly dependent on the BM microenvironment, particularly on CXCL12-abundant Reticular (CAR) cells, which provide a niche for maintenance of primitive cells. During B-ALL, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The same was suggested for MSC when RNAseq data were analyzed from our previous work available in E-MTAB-10838 https:// www.ebi.ac.uk/arrayexpress/experiments/E-MTAB-10838/ and when TLR8 expression was investigated by multiparametric flow cytometry in CD45 − CD73 + CD105 + CD90 + primary stromal cells (Figure 8(C), left and right panels) 17 Together, miR-146a-5p, miR-181b-5p, and miR-199b-3p are secreted by ALL cells inside exosomes into the BM microenvironment with apparently direct effect on both, residual normal hematopoietic cells, including innate immune cells, and MSC.…”
Section: A Proinflammatory Microenvironment Supported By Cytokine Sec...mentioning
confidence: 62%
See 2 more Smart Citations
“…The same was suggested for MSC when RNAseq data were analyzed from our previous work available in E-MTAB-10838 https:// www.ebi.ac.uk/arrayexpress/experiments/E-MTAB-10838/ and when TLR8 expression was investigated by multiparametric flow cytometry in CD45 − CD73 + CD105 + CD90 + primary stromal cells (Figure 8(C), left and right panels) 17 Together, miR-146a-5p, miR-181b-5p, and miR-199b-3p are secreted by ALL cells inside exosomes into the BM microenvironment with apparently direct effect on both, residual normal hematopoietic cells, including innate immune cells, and MSC.…”
Section: A Proinflammatory Microenvironment Supported By Cytokine Sec...mentioning
confidence: 62%
“…Our previous work has shown that ALL mesenchymal stromal cells (MSCs) display a proinflammatory profile with nuclear NF-κB translocation and contribute to an aberrant microenvironment through an increased secretion of cytokines including IL-1α, IL-6, IL-12p70, and TNFα. 15,17,22,23 Here, we report 3 miRNAs, which are up-regulated in ALL and contain the GU motifs between 18th and 21th positions, determinant for binding to the TLR8. The revealed ALL-miRNAs function as agonist TLR8 ligands, promoting inductive signals for a proinflammatory connection between tumor and normal early hematopoiesis in ALL cells.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hence, several protocols for bioengineering 3D HSC niches have been established for mouse and human HSC and LSC expansion [4,[103][104][105][106][107][108][109][110][111]. A well-designed artificial niche must be adaptable and scalable, facilitate selective incorporation of a variety of biochemical signals and allow the use of high-throughput or single-cell techniques, in addition to overcoming biomechanical and biotransport restrictions [68].…”
Section: Two-dimensional and Three-dimensional In Vitro Modelsmentioning
confidence: 99%
“…A well-designed artificial niche must be adaptable and scalable, facilitate selective incorporation of a variety of biochemical signals and allow the use of high-throughput or single-cell techniques, in addition to overcoming biomechanical and biotransport restrictions [68]. A big step towards the modeling of the leukemic niche was the possibility to grow leukemic cells as spheroids [107,112,113], or their implantation into polymer matrixes [37,109,112] or inside porous scaffolds [103,105,111,114]. The use of bioreactors or microfluidic devices further improved nutrient supply and increased the number of parameters involved on the niche building [115][116][117][118][119].…”
Section: Two-dimensional and Three-dimensional In Vitro Modelsmentioning
confidence: 99%